(untitled) (Balneo and PRM Research Journal, 2024)
Vitamin D deficiency is a significant global public health issue, even in regions with all year sun exposure. Currently, the scientific community has not yet reached a unanimous agreement regarding the optimum levels of vitamin D and the precise threshold values. Additional efforts are required to standardize the evaluation of vitamin D insufficiency and deficiency and to provide uniform treatment guidelines. Epidemiological studies have identified a broad spectrum of estimated prevalences in athletes. Their performance when participating in sports. depend on their muscles, heart and lung function. It seems that athletes have significantly lower levels of vitamin D compared to the general population. However, there is a lack of comprehensive studies and systematic reviews on this subject, making it challenging to reach conclusions due to variations in laboratory techniques and cut-off values. While there is an abundant of research on the supplementation of vitamin D and its benefits, it is challenging to provide general recommendations for athletes due to the limitations of extrapolation. However, there is a rather high occurrence of Vitamin D deficiency among individuals who engage in regular physical activity. Supplementing with Vitamin D helps prevents osteoporosis, bone fractures, enhances muscle strength, avoids lung infections, heart failure, and arrhythmias. It is generally safe when used in appropriate quantities, given its wide therapeutic range. Athletes can decrease the occurrence of training dropouts caused by infection, arrhythmias, muscular weakness and potentially prevent the inability to participate in competitions through correct nutrition and vitamin D supplementation.